Governing multicultural Brussels: paradoxes of a multi-level, multi-cultural, multi-national urban anomaly. Issue 12 (10th September 2018) - Bousetta, Hassan; Favell, Adrian; Martiniello, Marco
ABSTRACT: Updating our earlier work on Brussels as the paradigm of a multi-level, multi-cultural, multi-national city, and in the context of Brussels's recent troubled emergence as the epicentre of violent conflict between radical political Islam and the West, this paper sets out the paradoxical intersection of national (i.e. Flemish and Francophone), non-national and ethnic minority politics in a city placed as a multi-cultural and multi-national 'urban anomaly' at the heart of linguistic struggle of the two dominant Belgian communities. Brussels is one of the three Regions of the Belgian federal model alongside Flanders and Wallonia. It is also an extraordinarily diverse and cosmopolitan city, in which a mixed language Belgian population lives alongside very high numbers of resident non-nationals, including European elites, other European immigrant workers, and immigrants from Africa and Asia. After laying out the complex distribution of power and competences within the Belgian federal structure, we explore whether these structures have worked over the years to include or exclude disadvantaged ethnic groups. To better understand these processes, we introduce our view of the multi-level governance perspective.